Density of nesting sites and their use by two woodpecker species (Melanerpes rubricapillus y M. chrysauchen) (Piciformes: Picidae) along an urban gradient, Costa Rica. - Sandoval, Luis (2009)
I examined the density of nesting substrates potentially used by two woodpeckers (Melanerpes rubricapillus and M. chrysauchen) along an urban gradient, and their nest density in three sites with different human intervention in Golfito, Costa Rica. The urban and semi-urban sites had the lowest abundance of natural substrates for nesting, as expected by the effect of urban development. Nest abundance was greater in the semiurban site than in other sites, possibly in relation with a greater abundance of woodpeckers. Nests had a grouping distribution, which might reflect the preference of woodpeckers for nesting in natural substrates. The reduction of artificial and natural substrates in urban areas could decrease density population of these two woodpecker species.